Analytical Study of Beneficial Effects of Magnesium Sulfate for the Neuroprotection in Pre-Term Babies in Tertiary Care Hospital Bahawalpur: Magnesium Sulfate for the Neuroprotection - Bibi, Shabana; Uzma, Syeda; Sajjad, Rabia; Chaudhary, Sadia Zainab; Ashraf, Viqar; Moin, Sadaf (Pakistan Journal of Health Sciences, 2025)
Neonatal morbidity and mortality are greatly influenced by preterm birth. Magnesium sulfate (MgSO4) has been suggested as a neuroprotective therapy to reduce the negative consequences on neurodevelopment in preterm infants. Objective: To investigate how MgSO4 works to reduce the incidence of cerebral palsy as well as other neurodevelopmental impairments in preterm infants. Methods: This quasi experimental study was conducted at Tertiary Care Hospital Bahawalpur in the Department of Obstetrics and Gynecology from September 30, 2022 to March 29, 2023. This research involved 312 preterm infants. The infants were divided to a group of treatment with MgSO4 or compared with a group without MgSO4 exposure. The incidence of intraventricular hemorrhage (IVH), need for mechanical ventilation, neonatal mortality, as well as cerebral palsy were also measured and compared between the groups using Chi-square and T-tests. Results: The administration of MgSO4, dramatically reduced the rate of IVH (6.4%, 16%, p = 0.007 respectively treatment and control group) and neonatal mortality (3.2%, 10.3%, p = .013). It did not significantly affect the need for mechanical ventilation. This proved to be effective in reducing cerebral palsy by 21.8 percentage points (4.5% vs 26.3%, p<0.001). Conclusion: MgSO4 administration antenatally greatly decreases the risks of IVH and neonatal mortality while decreasing the incidence of cerebral palsy in preterm infants, thereby resulting more to be a 'gold standard' neuroprotective strategy in prenatal care.